Hubungan Kadar Pb dalam Darah dengan Kejadian Hipotiroidisme pada Wanita Usia Subur di Perkampungan Usaha Kecil dan Menengah Desa Pesarean Kabupaten Tegal - Novi Hidayati; Suhartono Suhartono; Nurjazuli Nurjazuli (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background: Hypothyroidism on women at childbearing age (WCA) can cause reproduction disorder, i.e. infertility,spontaneous abortion, impaired growth and development of foetus, placental abruption, and preterm delivery.Exposure tolead(Pb) at low lever contunuely for a long time willresult thyroid dysfunction. This research aimedtoprove that lead exposure is a risk factor for thyroid dysfunction among WCA in metal industrial of Pesarean inTegal districtMethods: Cross-sectional studyused32subjectsresearchatmetal industrial PesareanDistrictof Tegal. Pblevelsinthe bloodwas used asbiomakerofPbexposure. Thyroid dysfunction was determined based on the result ofTSH(Thyroid Stimulating Hormone). Confounding variables were also measured. These variables were age,length of stay, participation in hormonal contraception, iodine intake, pesticide exposure, exposure to cigarettesmoke, and employment history. Data would be analyzed using chi-square test at 0,05 level of significancy.Result: The prevalence of hypothyroidism among WCA was 25 %. Lead exposure was a risk factor for hypothyroidism(95 % CI, PR= 11,667(1,628- 83,597); and p-value = 0,002. The higher the degree of exposure, the greater therisk of having thyroid dysfunction. Based on data and the theory analysis, the pathogenesis of hypothyroidismwas suspected through the disruption of TPO function, D1 enzyme inhibition and D3 enzyme activation.Conclusion: Lead exposure was a risk factor for thyroid dysfunction among WCA in metal industrial township.Keywords: Leadexposure, hypothyroidism, blood lead level